Validation of specific inhalation challenge for the diagnosis of occupational asthma due to persulphate salts. Issue 10 (17th September 2004) - Muñoz, X; Cruz, M J; Orriols, R; Torres, F; Espuga, M; Morell, F
Abstract : Background: The significant value of tests used to certify the diagnosis of occupational asthma due to persulphate salts remains uncertain. Aims: To validate the specific inhalation challenge (SIC) test for the diagnosis of occupational asthma. Methods: Eight patients with occupational asthma due to persulphate salts, eight patients with bronchial asthma who were never exposed to persulphate salts, and ten healthy subjects were studied. Clinical history taking, spirometry, bronchial challenge with methacholine, skin prick testing to common inhalant allergens and persulphate salts, total IgE levels, and SIC to potassium persulphate were carried out in all subjects. The SIC used increasing concentrations of potassium persulphate (5, 10, 15, and 30 g) mixed with 150 g of lactose. Patients tipped the mixture from one tray to another at a distance of 30 cm from the face for 10 minutes in a challenge booth. Results: The SIC was positive in all subjects with persulphate induced asthma and in one patient with bronchial asthma who had never been exposed to persulphate salts. Sensitivity was 100% (95% CI 67.6 to 100) and specificity was 87.5% (95% CI 52.9–97.8) when patients with occupational asthma due to persulphate salts were compared with those with bronchial asthma never exposed to persulphate salts. Conclusions: SIC to persulphate salts performed according to the protocol described appears to be useful for the diagnosis of occupational asthma secondary to inhalation of this substance.